2004
DOI: 10.1182/blood.v104.11.3005.3005
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Second Acute Promyelocytic Leukemia (APL) Patient with the STAT5b-RARα Fusion Gene among PML-RARα-Negative Eastern Cooperative Oncology Group (ECOG) APL Protocol Registrants.

Abstract: In addition to the PML-RARα fusion gene, which accounts for >98% of APL cases, a common segment of 5′-truncated RARα has been found to fuse with the following 4 alternative genes: promyelocytic leukemia zinc finger (PLZF-RARα), nucleophosmin (NPM-RARα), nuclear mitotic apparatus protein (NUMA-RARα) and signal transducer and activator of transcription 5b (STAT5b-RARα). While recurrent cases of PLZF-RARα and NPM-RARα have been documented, there are only single case reports of NUMA-RARα and STAT5b-RARα. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Gallagher et al. identified one case with STAT5B–RARA in 22 PML – RARA negative APL cases (6). Xu et al.…”
Section: Discussionmentioning
confidence: 99%
“…Gallagher et al. identified one case with STAT5B–RARA in 22 PML – RARA negative APL cases (6). Xu et al.…”
Section: Discussionmentioning
confidence: 99%
“…With a great interest we read the report regarding the APL patient with STAT5B-RARa (3). To date, there are only three reported APL patients who harbor the STAT5B-RARa (3)(4)(5)(6), therefore, clinical features of this particular subtype, response to therapy and its pathogenesis remain to be determined. This study describes the fourth APL patient harboring the STAT5B-RARa.…”
mentioning
confidence: 99%
“…As a distinction to PML-RAR α APL, our study show that variant forms present with higher median WBC counts, and 40-50% could be classified as high-risk according to the Sanz's score. As per the literature review, only IRF2P2-RAR α APL had different features at diagnosis (3 out 5 cases were female and all had WBC < 5 × 10 9 /L) (Table 4) [7,[15][16][17][18][19][20][21][22][23][24][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61]. On the other hand, it has been suggested that CD56 could be frequently expressed in some variant APL forms [2,4], but this could not be confirmed in our series (CD56 available only in 5 patients).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, 35 additional APL patients with other RAR α fusion genes have been reported as follow: 12 with the signal transducer and activator of transcription 5 beta (STAT5B)-RARα, 6 with Transducin β-like 1 X-linked receptor 1 (TBLR1-RARα), 5 with interferon regulatory factor 2 binding proteins 2 (IRF2P2)-RARα, 2 with factor interacting with PAPOLA and CPSF1 (FIP1L1)-RAR α , 2 with signal transducer and activator of transcription 3 (STAT3)-RAR α , 2 with BCL6 Corepressor (BCOR)-RAR α , and 1 case of nuclear mitotic apparatus protein 1(NuMa1)-RARα, protein Kinase CAMP-Dependent Type I Regulatory Subunit Alpha (PRKAR1A)-RARα, nucleic acid binding protein 1 (NABP1)-RARα, general transcription factor II-I (GTF2I)-RARα, trafficking From ER To Golgi Regulator (TFG)-RARα, and fibronectin Type III Domain Containing 3B (FNDC3B)-RARα (Table 4) [7,[15][16][17][18][19][20][21][22][23][24][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60]. Male predominance was noted (25 patients), with variable age at presentation (median 43 years), in 15 out of 30 patients (50%) with WBC > 10 × 10 9 /L.…”
Section: Other Variant Aplmentioning
confidence: 99%
See 1 more Smart Citation